Uma linguagem de modelagem da interação para auxiliar a comunicação designer-usuário - Costa Neto, Macilon Araújo (2013)
The development of interactive systems involves several professionals and the integration between them normally uses common artifacts, such as models, that drive the development process. In the model-driven development approach, the interaction model is an artifact that includes the most of the aspects related to what and how the user can do while he/she interacting with the system. Furthermore, the interactive model may be used to identify usability problems at design time. Therefore, the central problematic addressed by this thesis is twofold. In the first place, the interaction modeling, in a perspective that helps the designer to explicit to developer, who will implement the interface, the aspcts related to the interaction process. In the second place, the anticipated identification of usability problems, that aims to reduce the application final costs. To achieve these goals, this work presents (i) the ALaDIM language, that aims to help the designer on the conception, representation and validation of his interactive message models; (ii) the ALaDIM editor, which was built using the EMF (Eclipse Modeling Framework) and its standardized technologies by OMG (Object Management Group); and (iii) the ALaDIM inspection method, which allows the anticipated identification of usability problems using ALaDIM models. ALaDIM language and editor were respectively specified and implemented using the OMG standards and they can be used in MDA (Model Driven Architecture) activities. Beyond that, we evaluated both ALaDIM language and editor using a CDN (Cognitive Dimensions of Notations) analysis. Finally, this work reports an experiment that validated the ALaDIM inspection method